Reading and writing skills - Menoy, Jesus Z.; Constantino, Guia F. (Mandaluyong City, Philippines : Books Atbp. Publishing Corp, 2016)
This book titled Reading and Writing Skills was written as an answer to the need for a book in one of the core subjects in senior high school, that is, English, under the K-to-12 basic education curriculum.- - Preface.
Lesson 1 - Text as connected discourse -- Lesson 2 - Techniques in organizing information -- Lesson 3 - Patterns of development -- Lesson 4 - Organization -- Lesson 5 - Coherence and cohesion -- Lesson 6 - Language use -- Lesson 7 - Mechanics -- Lesson 8 - Text and context connections -- Lesson 9 - Purposeful writing in the disciplines -- Lesson 10 - Purposeful writing for the profession.
Includes bibliographical references.
Keywords: READING